ANALISIS POSISI PUSAT KOTA KENDARI BERDASARKAN ASPEK AKSESIBILITAS WILAYAH - Rianse, Usman (Jurnal Perencanaan Wilayah, 2014)
Research indicates that the stadia development of Kendari city centers and community activities are inclined to change, especially for the villages that have not been examined closely to determine the actual position or the highest order within the city of Kendari. Based on the background of the problem, the purpose of this study was to analyze the orders of each village; to analyze the typologies and models of accessibility; and to analyze the location of the central bussiness district areas within the city of Kendari. This research is of explanatory or descriptive quantitative research. The populations of the study were all villages in the city of Kendari. The sample comprised 64 villages. Secondary data analysis suggests that the order of the city as measured by the total population within each of the village areas of the municipality of Kendari, using Christaler, ZIFT, and Rank Size Rule methods, is as follows: typologically, there were as many as 30 very fast growing villages (46.88%), 15 fast growing villages (23.44%), 11 medium growing villages (17.19%), 6 slow growing villages (9.38%), and 2 very slow growing villages (3.13%). The location of the central bussiness districts in the city of Kendari began to be concentrated in Mandonga, Wua-Wua, Kadia, Poasia and Puwatu.